Escalation and Nuclear Option - Brodie, Bernard, 1910-1978 (Book collections on Project MUSE., 2015)
This work stresses the importance, in making any choice of strategies-including the decision to use or refrain from using nuclear weapons-of gauging the intent behind the opponent's military moves. Dr. Brodie also suggests that the use or threat of use of tactical nuclear weapons may lead to de-escalation, that is, may check rather than promote the expansion of hostilities. The author applies his ideas about escalation to several imagined situations, examining them in relation to experiences in Europe, in the second Cuba crisis, and in Asia. Originally published in 1966. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.